Multi-Climate Simulation of Temperature-Driven Efficiency Losses in Crystalline Silicon PV Modules with Cost–Benefit Thresholds for Evaluating Cooling Strategies - Bitian Jiang; Christi Madsen (Energies)
We explored the impact of high operating temperatures for monocrystalline silicon photovoltaic (PV) modules which dominate the market. Using nine years of hourly climate data with the System Advisor Model (SAM), we examined temperature impacts and cooling potential benefits across three climate zones in the United States. Assuming that cooling approaches can achieve a constant temperature decrease of ΔT independent of irradiance and environmental conditions, our simulations show that a ΔT = 10 °C temperature reduction could improve energy yield by almost 3% annually. Cooling technologies have the strongest impact during the hottest months, with even a 5 °C reduction raising efficiency by nearly 10%. When the minimum temperature of the cooled module is constrained to the ambient temperature, ΔT = 20 °C boosts the hottest month energy yield by over 25%. For economically viable cooling systems, the cooling cost should be much less than the break-even cost. We estimate break-even costs of USD 25–40/m2 for 10 °C and USD 40–60/m2 for 20 °C cooling for the locations simulated. For ΔT > 20 °C, the added energy yield shows diminishing returns with minimum increase in break-even costs.